2021
DOI: 10.1155/2021/5258782
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Luminance and Contrast Variation on Stereoacuity Measurements Using Smartphone Technology

Abstract: Owing to the limitations of printed stereoacuity tests, the effects of luminance and contrast on stereopsis have not yet been sufficiently investigated, despite its important implications in designing stereoacuity measuring instruments, particularly for electronic devices. A stereopsis measurement system was established using two 4 K smartphones and a phoropter to evaluate the effects of luminance and contrast variations on the stereoacuity test. Seventeen young subjects with normal visual acuity and stereopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…During the testing process, certain factors, which ordinarily exert a negligible effect on stereopsis under normal vision conditions, may potentially influence the measurement outcomes under conditions of diminished vision. For instance, brightness ( Liu, Xu, Wang, & Wu, 2021 ), contrast ( Chen, Chen, & Tyler, 2016 ), and target size may play a role. These variables underscore the complexity of accurately assessing the impact of vision loss on stereopsis and point to the need for further research to elucidate the interplay of these factors fully.…”
Section: Discussionmentioning
confidence: 99%
“…During the testing process, certain factors, which ordinarily exert a negligible effect on stereopsis under normal vision conditions, may potentially influence the measurement outcomes under conditions of diminished vision. For instance, brightness ( Liu, Xu, Wang, & Wu, 2021 ), contrast ( Chen, Chen, & Tyler, 2016 ), and target size may play a role. These variables underscore the complexity of accurately assessing the impact of vision loss on stereopsis and point to the need for further research to elucidate the interplay of these factors fully.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al also found that brightness and contrast were not significant factors affecting stereopsis. 24 However, further studies are needed to investigate the long-term effects of interocular contrast differences caused by multifocal IOL implantation on the recovery of stereopsis function postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to facilitate fusion, two approximately 5.5ΔBO Risley prisms were positioned in front of both eyes ( Fig. 1A ) ( Liu et al, 2021 ; Xu, Liu & Wu, 2022 ).…”
Section: Methodsmentioning
confidence: 99%